2007
DOI: 10.1007/s11136-007-9231-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of response bias on self-reported quality of life among childhood cancer survivors

Abstract: CCS show a biased response style, indicating a systematic tendency to deny difficulties on QOL measures. This may complicate QOL studies by inflating survivors' reports of their socio-emotional functioning. Understanding how response bias develops may help us learn more about cancer survivors' adaptation to illness, and the effects of the illness experience on their perceptions of QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
63
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 81 publications
3
63
0
5
Order By: Relevance
“…On the other hand, there are some data indicating that most people show life satisfaction even with very poor health states, such as amputation (38,39), and several studies indicating that survivors of cancers in general and childhood cancers in particular may be biased reporters and tend to deny difficulties and overestimate their positive health and satisfaction (40)(41)(42)(43)(44). O'Leary et al (45) reported from a sample of Dana-Farber patients participating in CCSS that survivors had a strong tendency toward an enhanced self-appraisal and such bias had a differential effect on self-reported physical and emotional quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are some data indicating that most people show life satisfaction even with very poor health states, such as amputation (38,39), and several studies indicating that survivors of cancers in general and childhood cancers in particular may be biased reporters and tend to deny difficulties and overestimate their positive health and satisfaction (40)(41)(42)(43)(44). O'Leary et al (45) reported from a sample of Dana-Farber patients participating in CCSS that survivors had a strong tendency toward an enhanced self-appraisal and such bias had a differential effect on self-reported physical and emotional quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…19 It is important to note that previous studies of HRQOL in YASCC largely relied on quantitative data collected by existing instruments. 21,22 Theoretically, quantitative methods are useful for comparing HRQOL across subgroups of cancer survivors given the established framework or instruments with pre-specified domains of HRQOL (e.g., physical, psychological, and social functioning). 21,22 In contrast, qualitative methods allow for a more thorough exploration of the unique HRQOL issues for YASCC that have traditionally been neglected in quantitative instruments.…”
mentioning
confidence: 99%
“…21,22 Theoretically, quantitative methods are useful for comparing HRQOL across subgroups of cancer survivors given the established framework or instruments with pre-specified domains of HRQOL (e.g., physical, psychological, and social functioning). 21,22 In contrast, qualitative methods allow for a more thorough exploration of the unique HRQOL issues for YASCC that have traditionally been neglected in quantitative instruments. In other words, qualitative methods may facilitate a greater understanding of HRQOL for this population by allowing the researcher to identify and explore the domains of HRQOL that are relevant to this population.…”
mentioning
confidence: 99%
“…Third, self-reported events and response bias can lead to underestimation of problems by denial of difficulties in the survivor population. 45 Additionally, we do not have the ability to assess the validity of the various outcomes included in the analysis, irrespective of whether the respondent was the survivor or a proxy. While CCSS investigators have had excellent success in validating selected outcomes, such as second malignancies, our success in achieving medical record validation for other major outcomes has been limited.…”
mentioning
confidence: 99%